Pendekatan Whole Language melalui Multi Media dalam Peningkatan Keterampilan pembelajaran Bahasa Arab bagi Mahasiswa Prodi Pendidikan Bahasa Arab, Fakultas Tarbiyah dan Keguruan UIN Sunan Ampel Surabaya - Muflihah Mufilhah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
An important problem faced by lecturers in learning Arabic is technology-based learning or through multimedia. Therefore, the author examines this through research to find out a number of issues, namely: 1) How to design learning with a whole language approach through Multi Media in improving Arabic language skills for Arabic education department at Tarbiyah and Teacher Training Faculty of UIN Sunan Ampel Surabaya? 2) How is the implementation of learning with the whole language approach through Multi Media in improving Arabic language skills for students of Arabic education department at Tarbiyah and Teacher Training Faculty of UIN Sunan Ampel Surabaya? The results of this study are that the implementation of learning with the whole language approach through multimedia is in class D as an experimental class, the researcher also implements learning by not using the whole language approach through Multi Media as a comparison class that is in class B and based on the results of calculations performed using applications Minitab 16 can be seen that the value of the t-test from the pre-test and post-test table in the experimental class or class D is 10.99 and the value of the t-count from the class B pre-test and post-test table is 5.75.